KOLABORASI GURU DAN KEPALA SEKOLAH DALAM MENJAGA MUTU PENDIDIKAN DI SDN 04 SANGGAU - Dayang Marniawarsih, Wahab; Sugeng Listyo Prabowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the collaboration between teachers and the school principal in maintaining educational quality at SDN 04 Sanggau, West Kalimantan. The problem lies in the need for synergistic working relationships to address educational challenges in resource-limited schools. Using a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and document analysis. The results show collaboration occurs in three main areas: program planning, teaching implementation, and evaluation. Teachers actively participate in school meetings, lesson planning, and program development, while the principal acts as a facilitator and motivator. Joint evaluations are conducted regularly to reflect on learning outcomes and determine improvements. Despite obstacles such as administrative burdens and differing perceptions of roles, collaboration is maintained through open communication and participative leadership. The study concludes that effective collaboration between principals and teachers plays a crucial role in building a positive school culture and sustaining educational quality, especially in geographically and socially challenged regions like Sanggau. These findings are expected to serve as policy and practice references in similar contexts.